RUANG PUBLIK DAN PEREMPUAN DI KOREA SELATAN - Ladyanna, Sonezza (MUWAZAH, 2013)
Abstract : This article discusses the public space in South Korea relating to women's rights. The purpose of this article is to investigate the existence of friendly public spaces for women. The researcher wants to know how to improve and equip the facilities in order to make friendly public spaces for women. This research found that the public spaces on campus and public toilets have sufficient rights of women so that women can feel comfortable. The conducive of public spaces supported by legal professionals can control a person's social behavior in addition to an effective moral education. Abstrak : Artikel ini membahas ruang publik di Korea Selatan yang berkaitan dengan hakhak perempuan. Tujuan artikel ini adalah untuk mengetahui keberadaan ruang publik yang ramah bagi perempuan. Peneliti ingin mengetahui bagaimana memperbaiki dan melengkapi fasilitas untuk membuat ruang publik yang ramah bagi perempuan. Penelitian ini menemukan bahwa ruang publik di kampus dan toilet umum memiliki hak yang memadai sehingga perempuan bisa merasa nyaman. Ruang publik yang kondusif didukung dengan hukum yang profesional juga dapat mengendalikan perilaku sosial seseorang di samping pendidikan moral yang efektif.